Difference between carbohydrate antigen 19‐9 and fluorine‐18 fluorodeoxyglucose positron emission tomography in evaluating the treatment efficacy of neoadjuvant treatment in patients with resectable and borderline resectable pancreatic ductal adenocarcinoma: Results of a dual‐center study. Issue 3 (17th December 2020) - Akita, Hirofumi; Takahashi, Hidenori; Eguchi, Hidetoshi; Asukai, Kei; Hasegawa, Shinichiro; Wada, Hiroshi; Iwagami, Yoshifumi; Yamada, Daisaku; Tomimaru, Yoshito; Noda, Takehiro; Gotoh, Kunihito; Kobayashi, Shogo; et al.
Abstract: Background: An accurate evaluation of neoadjuvant treatment is important to maximize the prognostic benefit of this strategy in each individual patient. The main aim of the present study is to investigate the difference between carbohydrate antigen 19‐9 and fluorine‐18 fluorodeoxyglucose positron emission tomography (FDG‐PET) in evaluating the response to neoadjuvant treatment for resectable and borderline resectable pancreatic ductal adenocarcinoma (PDAC) patients. Methods: Pancreatic ductal adenocarcinoma patients with positive standard uptake values (SUV) on FDG‐PET before neoadjuvant chemoradiotherapy (NACRT) were enrolled (n = 141). In all patients, CA19‐9 and FDG‐PET were evaluated before the initiation of and after the completion of NACRT. The statuses of CA19‐9 and FDG uptake alterations during NACRT were assessed in association with survival and tumor recurrence profiles. Results: A favorable response in each CA19‐9 and FDG‐PET was significantly related to better survival, respectively, than the unfavorable response (44.3% vs 19.5%, P  < .001 and 45.8% vs 24.6%, P  < .001). The status of CA19‐9 was significantly associated with the incidence of distant recurrence whereas the status of FDG‐PET was significantly associated with the incidence of local recurrence, and only patients with a favorable response in both CA19‐9 and PET statuses showed a significantly better survival than the others (5‐year survival: 56% vs 24%, P  < .001), and those with unfavorable response in either of CA19‐9 or PET status showed similar poor survival to those with unfavorable in both ( P = .164). Conclusion: CA19‐9 and PET evaluation provided oncologically different risk assessments in terms of tumor recurrence profile, and favorable response in both CA19‐9 and FDG‐PET were necessary to achieve prognostic benefit from NACRT. Abstract : CA19‐9 and PET evaluation provided oncologically different risk assessments in terms of tumor recurrence profile in NACRT for resectable and borderline resectable PDAC. The status on CA19‐9 and PET was associated with different profiles of tumor recurrence. Only patients with a favorable response in terms of both CA19‐9 (normalization) and PET status (>50% decrease in SUV‐max) after NACRT gained the optimal prognostic benefit.